Efficacy and Safety of First-Line Treatment Strategies for Anaplastic Lymphoma Kinase-Positive Non-Small Cell Lung Cancer: A Bayesian Network Meta-Analysis - Peng, Ling; Lu, Dafeng; Xia, Yang; Hong, Shaodong; Selvaggi, Giovanni; Stebbing, Justin; Sun, Yilan; Liang, Fei (Frontiers in Oncology, 2021)
Background Targeted therapies have led to significant improvement in the management and prognosis of anaplastic lymphoma kinase (ALK)-positive non-small cell lung cancer (NSCLC). We performed a network meta-analysis of frontline treatment options of ALK-positive NSCLC to provide clinical guidance. Methods PubMed, Embase, ClinicalTrials.gov, and international conference databases were searched to identify relevant trials from inception to June 30, 2021. Phase III randomized controlled trials (RCTs) comparing treatments for patients with ALK-positive advanced NSCLC in the first-line setting were included in a Bayesian network meta-analysis. Eligible studies reported at least one of the following clinical outcomes: progression-free survival (PFS), overall survival (OS), risk of the central nervous system (CNS) progression, adverse events (AEs) of grade (G) 3 or higher (G3 AEs), or serious AEs (SAEs). Hazard ratios (HRs) and CI for primary outcome of PFS and secondary outcome of OS and risk of CNS progression were obtained. A multivariate, consistency model, fixed-effects analysis was used in the network meta-analysis. Data on G3 AEs and SAEs were abstracted and meta-analyzed. Risk of bias (RoB) was assessed using the Cochrane Collaboration’s tool. Results Nine RCTs comprising 2,484 patients were included with seven treatments: alectinib, brigatinib, ceritinib, crizotinib, ensartinib, lorlatinib, and chemotherapy. Compared with chemotherapy, ALK-tyrosine kinase inhibitors (TKIs) significantly prolong PFS and reduced risk of CNS progression except for ceritinib. Lorlatinib appears superior at reducing risk of CNS progression. None of the ALK-TKIs have a significantly prolonged OS as compared with chemotherapy. Lorlatinib increases the risk of G3 AEs as compared with alectinib (odds ratio 4.26 [95% CrI 1.22 to 15.53]), while alectinib caused the fewest G3 AEs. Conclusions Lorlatinib is associated with the highest PFS benefit and lowest risk of CNS progression benefits for patients with advanced ALK-positive NSCLC, compared with other first-line treatments, but with higher toxicity. The implementation of a newer generation of ALK-TKIs in the first-line treatment of ALK-positive NSCLC into current clinical practice is evolving rapidly.